Implementasi Proses Rekrutmen Dan Seleksi Pada Karyawan Di UKM Early Coffe Batam - Mualifah Nurhidayati; Yuli Indah Fajar Dini (Jurnal Visi Pengabdian Kepada Masyarakat, 2024)
The background raised in this service activity is to provide an understanding of the right recruitment and selection process or stages for Early Coffee and the use of social media to advertise job vacancies in accordance with the required positions. The purpose of this service activity is so that Early Coffee can find out how to recruit employees who are in accordance with the required positions so that the process of selecting new employees will be appropriate and can improve employee work performance because they work according to their fields. The method used in this activity is an introduction to the recruitment and selection process with several stages, making prospective employee forms and explaining the job description of each employee. The results obtained in this activity are that Early Coffee is very careful and strategic in selecting suitable employees and social media is a means for Early Coffee to open job advertisements to the wider community while marketing its culinary beverage business